Pengaruh Pengaruh Pengetahuan Pajak, Sanksi Pajak, dan Kualitas Pelayanan Pajak Terhadap Kepatuhan Wajib Pajak dalam Membayar Pajak Bumi dan Bangunan: Pengaruh Pengetahuan Pajak, Sanksi Pajak, dan Kualitas Pelayanan Pajak Terhadap Kepatuhan Wajib Pajak dalam Membayar Pajak Bumi dan Bangunan - Merry, Merry; Lina Fuadah (Journal Of Islamic Economics And Finance, 2024)
This research aims to evaluate the influence of tax knowledge, tax sanctions, and the quality of tax services on taxpayer compliance, both independently and collectively. Taxes function as a funding mechanism for a country's progress with the aim of improving the standard of living of regional communities. Rural and Urban Land and Building Tax (PBB-P2) refers to taxes imposed on authorities, owners and managers of buildings in the form of individuals or companies, with the exception of areas used in mining, forest and plantation operational activities. Although land and building taxes are considered a very promising source of income for regional support, regions still face big challenges in collecting these taxes effectively. This research uses quantitative methodology. The research sample consisted of 100 respondents who were selected using a simple random selection technique. This research uses primary data. The IBM SPSS 26 software package was used to carry out data processing and multiple linear regression analysis. The t test results indicate that tax knowledge, tax sanctions, and the quality of tax services influence taxpayer compliance. The results of the F test indicate that taxpayer compliance is significantly influenced by tax knowledge, tax sanctions, and the quality of tax services, simultaneously.